The Effect of Sorbitol Addition in Bioplastic from Cellulose Acetate (Sugarcane Bagasse)-Chitosan - Zidni Azizati; Iseh Muhammad Zaenal Afidin; Lutfi Aditya Hasnowo (Department of Chemistry Faculty of Science and Technology Walisongo, 2022)
This study aimed to determine the effect of sorbitol addition into cellulose acetate-chitosan bioplastic and its biodegradation properties. Cellulose was isolated from the pulp of sugarcane bagasse and acetylated to be cellulose acetate. Cellulose acetate was characterized by FTIR, the results of FTIR characterization contained C=O and C-O functional groups with wavenumbers of 1644.99 cm-1 and 1059.86 cm-1 which indicated the formation of cellulose acetate. Cellulose acetate-chitosan bioplastic and cellulose acetate-chitosan-sorbitol bioplastic has been successfully synthesized and characterized. The results of FTIR characterization showed that bioplastics had C=O and C-O functional groups at wavenumbers of 1644.99 cm-1, 1059.86 cm-1 which was indicated as cellulose acetate and N-H functional group at wavenumber of 1559.66 cm-1 which was indicated as the presence of chitosan in bioplastics and there is an increase in absorption intensity of the O-H functional group which indicates that sorbitol has been successfully added to bioplastics. The addition of sorbitol could improve the percent of elongation from 14.0635% to 19.9379% and decrease the tensile strength from 6.3049 MPa to 0.6309 MPa. It also could increase water absorption from 16.68% to 88.73%, and could accelerate the bioplastic degradation process from 24 days to 8 days.